Vendsysselske Bronzealderfund - Friis, Palle (Kuml, 1961)
Bronze Age Finds from Vendsyssel. Three valuable Bronze Age finds have been received in 1960 by the Historical Museum of Vendsyssel: 2 single finds of bronze swords and a collection of 45 bronze objects found in an earthen vessel. The Bronze Sword from Uggerby (fig. 1) was found by a fisherman in the river Uggerby. The sword is 63 cm long (24.8 in.) and has a slightly convex blade considerably thicker at the centre. The blade is terminated by a trapeze-shaped plate onto which the hilt is secured by four rivets that pierce the base of the hilt, which is cast in one piece with an oval bar. This bar was originally covered with bronze and horn (or bone) rings, of which four bronze rings are preserved. The pommel is terminated by a circular plate crested wih three parallel lines. The sword is dated to period II and is possibly of Eastern Central European provenance. The Bronze Sword from Måstrup (fig. 3) was found at a depth of 2-3 metres in Måstrup Bog. It was situated pointing downwards in a practically vertical position. It is a tanged sword, 71.5 cm in length (29.9 in.) with a slim, straight blade. The tang has high, curved edges and, in the curve nearest the blade, is pierced by four rivet holes. On the tang, the remains of a whitish mass, probably lead, can be seen. This type of sword belongs to period II and is probably of foreign origin. The Sæsing Find consists of 45 pieces of bronze, found in an earthen jar, at a depth of approximately 50 cm, in sandy clay soil, while digging out the foundations of a house in the village of Sæsing. The find can be divided into two groups consisting of women's jewellery and harness mountings. The women's jewellery consists of: 2 hollow-cast gorgets, each made up of three rings slantingly grooved (fig. 5), 3 pendant vessels (fig. 6, 7, 8), all with rounded bases, sloping shoulders and vertical necks. A piece of a wooden lid with a bolt attached, belonging to the bowl fig. 6-7, right, was also found. It corresponds in form to bronze lids known from earlier finds. 3 armlets (fig. 10) with slightly arched transverse section. One has a tripartite central rib, the other two have only a single central rib but have protruding strips along the edges. A spectacle fibula (fig. 11) with a solid how and undecorated, slightly domed plates. The pin is terminated by an ornamented disc. 13 ornamental buttons, probably a set, are, possibly, a belt decoration, as 12 similar buttons have been found in a grave, mounted on a leather strap. They can, however, belong to the harness mountings. The group of harness mountings consists of: 4 bit branches, slightly curved, and having a socket at one end through which a transverse rivet has been stuck. The oval central perforation shows heavy signs of wear. A similar bit is known from a find from Nymö in Skåne. 5 wheel-shaped pendants may belong to this group also, as they may have hung from the bit as jingle plates. 4 ornamental studs which have, presumably, been mounted on harness. There was a similar stud in the Nymö find. 1 knobbed sickle and several small pieces of bronze could not be classed in either of the above two groups. The find as a whole belongs to period IV. Palle Friis.